1998
DOI: 10.1051/aas:1998360
|View full text |Cite
|
Sign up to set email alerts
|

The intraday variability in the radio-selected and X-ray-selected BL Lacertae objects

Abstract: Abstract. Seven BL Lac objects have been photometrically observed in an effort to study the difference of optical intraday variability between the radio-selected BL Lac objects (RBLs) and X-ray-selected BL Lac objects (XBLs). The objects we observed are selected arbitrarily. They are four RBLs, PKS 0735+178, PKS 0754+101, OJ 287 and BL Lac, and three XBLs, H 0323+022, H 0548−322 and H 2154−304. During the observation all of them exhibited microvariation, and H 0323+022 and H 0548−322 sometimes showed brightnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…In a study of several BL Lac objects consisting of the radio-selected BL Lac objects (RBLs) and X-ray-selected BL Lac objects (XBLs), Bai et al [11] found that XBLs show more frequent microvariability than RBLs. Kraus et al [12] observed that intraday variations are common in RL AGNs and that the flux variations are often accompanied by similar variations in the linear polarization.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of several BL Lac objects consisting of the radio-selected BL Lac objects (RBLs) and X-ray-selected BL Lac objects (XBLs), Bai et al [11] found that XBLs show more frequent microvariability than RBLs. Kraus et al [12] observed that intraday variations are common in RL AGNs and that the flux variations are often accompanied by similar variations in the linear polarization.…”
Section: Introductionmentioning
confidence: 99%
“…The periodic variabilities of blazars have been investigated extensively in the optical band (e.g., Bai et al 1998Bai et al , 1999Fan & Lin 2000;Xie et al 2008;Li et al 2009;Urry 2011;King et al 2013;Zhang et al 2014;Bhatta et al 2016;Fan et al 2016). An interesting case is that of OJ 287, which has a ∼12 yr period cycle (Kidger et al 1992;Valtonen et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, variability of blazars in radio to optical bands on diverse time scales has been reported in a large number of papers (e.g. Miller et al 1989;Courvoisier et al 1995;Heidt & Wagner 1996;Takalo et al 1996;Sillanpää et al 1996aSillanpää et al , 1996bBai et al 1998Bai et al , 1999Fan et al 1998Fan et al , 2002Fan et al , 2007Xie et al 2002a;Gupta et al 2004;Ciprini et al 2003, 2007 andreferences therein).…”
Section: Introductionmentioning
confidence: 99%